PENGARUH STRUKTUR MODAL, PROFITABILITAS, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (Studi Kasus Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2015-2017) - Noer Fadhilah Rahman; Ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThis study aims to find out and analyze how the influence of capital structure, profitability, and firm size on the value of banking companies listed on the Indonesian stock exchange in 2015-2017, simultaneously and partially. The population in this study is from data obtained from the financial statements of the Indonesia Stock Exchange as many as 43 companies. And the sampling technique in this study is the purposive sampling technique, with 25 sample data obtained. The analysis was carried out using quantitative descriptive analysis.The results of this study indicate that the capital structure does not have a significant negative effect on the value of banking companies, profitability has a significant positive effect on firm value, and firm size has a significant negative effect on firm value. Based on the results of the research obtained, it is recommended for companies to be able to improve the company's financial performance. And from the results of this study has a contribution in order to maximize company value and add insight into the factors that influence the decision to invest.Keywords: Capital structure, profitability, company size and company value